The Presence of Absence. Transgenerational Local Memory of the Holocaust Among Hungarians - Richárd Papp; György Csepeli (Studia Humanistyczne AGH)
The paper reports on the results of a non-representative focus group research aimed at exploring the local memory of the Holocaust in Hungary. The research took place between 2021 and 2024, almost 80 years after the events of 1944, at the historical moment when communicative memory is transforming into cultural memory. The sites of the research were villages, small and medium-sized towns, and the capital, precisely those scenes where the drama of the Holocaust took place in the summer of 1944. The results of the research showed that the Jews disappeared, but signs of their former presence remained. The traces of past Jewish life, however, became increasingly obscured over time in the minds of the successive generations.